The Optimal Level of Social Security Benefits - Feldstein, Martin (Quarterly Journal of Economics, 1985)
The optimal level of Social Security benefits depends on balancing the protection that these benefits offer to those who have not provided adequately for their own old age against the welfare costs of distorting economic behavior. The primary such cost is the distortion in private saving. The present paper derives the level of Social Security benefits that is optimal in three basic cases. In the first section of the paper, the optimal level of benefits is derived for an economy in which all individuals do not anticipate retirement at all and therefore do not save. The second and third sections then derive the optimal benefits for economies with two different definitions of attitudes toward retirement and saving.